Homozygous CALR Mutation in Primary Myelofibrosis and Its Effect on Disease Phenotype: A Case Report and Review of the Literature - Qurratulain Rizvi; Uzma Zaidi; Saba Shahid; Shariq Ahmed; Tahir Shamsi (Case Reports in Hematology)
Somatic mutations in CALR gene have been reported in 60%–88% of patients with essential thrombocythemia (ET) and primary myelofibrosis (PMF) who are negative for JAK2 and MPL mutations. Most of the CALR mutations analyzed to date are heterozygous mutations in exon 9 of the gene. Homozygosity in CALR gene is rarely reported, and its association with clinical behavior of disease and impact on outcome of patients is not studied so far. We herein report a case of intermediate-2 risk PMF (according to IPSS) diagnosed with homozygous mutation (c.1139delA p.E380fs∗50) in CALR gene having severe disease manifestations at presentation.